EFEKTIVITAS KEMANDIRIAN ANAK BERKEBUTUHAN KHUSUS MELALUI METODE PEMBIASAAN - Felix Trisuko Nugroho, Sarah Talita Primadani, Michael Widya Christian (JIP: Jurnal Ilmu Pendidikan, 2024)
This study aims to evaluate the effectiveness of the habituation method in increasing the independence of children with special needs. The habituation method, which involves repetition, consistency, and positive reinforcement, has been widely applied in various educational and therapeutic contexts for children with special needs. The research methodology uses a one-group pre-test-post-test design. A total of 30 children with special needs from three inclusive schools in Madiun participated in this study. The results of this study include the design of the habituation method carried out in several steps with a focus on how to accustom children with special needs to their respective levels of independence, especially in daily life. Steps that can be taken in designing the habituation method to increase the independence of children with special needs include creating lesson plans (RPPH) tailored to independence indicators, which are then assessed through observation supervised by their teachers. Changes in the independence of early childhood using the habituation method were observed. There is effectiveness in children's independence with the habituation method. However, a deeper empirical evaluation is still needed to ensure the benefits and effectiveness of this method.